AAV9 Delivery of shRNA to the Mouse Heart. Issue 1 (1st July 2016) - Wakimoto, Hiroko; Seidman, J.G.; Foo, Roger S.Y.; Jiang, Jianming
Abstract: RNA interference (RNAi) is a rapid approach to dissect loss‐of‐function phenotype for a gene of interest. However, it is challenging to perform RNAi in specific organs and tissues in vivo. Engineered viruses can provide a useful tool for delivery of small RNAs in vivo. Recombinant adeno‐associated viruses (rAAVs) are the preferred method for delivering genes or gene modulators to target cells due to their high titer, low immune response, ability to transduce many types of cell, and overall safety. In this unit, we describe protocols for use of rAAVs as a cargo to deliver miRNA backbone‐based shRNA controlled by a cardiac‐specific promoter into the mouse heart. © 2016 by John Wiley & Sons, Inc.